Concurrent left ventricular assist device (LVAD) implantation and percutaneous temporary rvad support via cardiacassist protek-duo tandemheart to preempt right heart failure - Schmack, Bastian; Weymann, Alexander; Popov, Aron-Frederik; Patil, Nikhil Prakash; Sabashnikov, Anton; Kremer, Jamila; Farag, Mina; Brcic, Andreas; Lichtenstern, Christoph; Karck, Matthias; Ruhparwar, Arjang (Medical science monitor. Basic research, 2016)
Right ventricular failure (RVF) is an unfortunate complication that continues to limit outcomes following durable left ventricular assist device (LVAD) implantation. Despite several ‘RVF risk scores’ having been proposed, preoperative prediction of post-LVAD RVF remains a guesstimate at best. Current strategies for institution of temporary RVAD support are invasive, necessitate additional re-thoracotomy, restrict postoperative mobilization, and/or entail prolonged retention of prosthetic material in-situ. The authors propose a novel surgical strategy comprising simultaneous implantation of a permanent LVAD and percutaneous TandemHeart® plus ProtekDuo® to provide temporary RVAD support and preempt RVF in patients with impaired RV function.